2009
DOI: 10.1001/archgenpsychiatry.2009.114
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of CRHR1 Gene Variants on the Development of Adult Depression Following Childhood Maltreatment

Abstract: Context A previous study reported a gene × environment interaction in which a haplotype in the corticotropin-releasing hormone receptor 1 gene (CRHR1) was associated with protection against adult depressive symptoms in individuals who were maltreated as children (as assessed by the Childhood Trauma Questionnaire [CTQ]). Objective To replicate the interaction between childhood maltreatment and a TAT haplotype formed by rs7209436, rs110402, and rs242924 in CRHR1, predicting adult depression. Design Two prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
232
3
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(278 citation statements)
references
References 40 publications
19
232
3
22
Order By: Relevance
“…Likewise, the CTQ taps negative events during childhood and adolescence, whereas CFA refers to the first 11 years of life. Similar discrepant G 9 E findings involving the CTQ and objective measures of childhood adversity have previously been reported (Laucht et al 2012;Polanczyk et al 2009). These authors suggested that, instead of the objective occurrence of adverse events, the emotional memories associated with adversity may be important in a gene by adversity interaction with regard to depression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Likewise, the CTQ taps negative events during childhood and adolescence, whereas CFA refers to the first 11 years of life. Similar discrepant G 9 E findings involving the CTQ and objective measures of childhood adversity have previously been reported (Laucht et al 2012;Polanczyk et al 2009). These authors suggested that, instead of the objective occurrence of adverse events, the emotional memories associated with adversity may be important in a gene by adversity interaction with regard to depression.…”
Section: Discussionsupporting
confidence: 83%
“…While the CTQ assesses memories of different types of childhood maltreatment, CFA covers qualitatively different stressors, which do not address maltreatment directly, but pertain to more adverse family circumstances such as marital discord or early parenthood. Given the role of the amygdala in emotional memory, we expected to find greater effects with regard to the CTQ, which has previously been related to emotional memory reactivation (Polanczyk et al 2009). Second, we extended previous work by investigating connectivity patterns and volumetric differences in the amygdala.…”
Section: Introductionmentioning
confidence: 97%
“…FKBP5 has also been associated with an increased risk of depression during adulthood among individuals who suffered from child abuse (Appel et al, 2011). Similarly, SNPs from the corticotrophin-releasing hormone receptor (CRHR1) gene, which helps mediate HPA axis response to stress, have been linked to the onset and course of PTSD in children (Amstadter et al, 2011), as well as increased risk of developing PTSD symptoms and depression during adulthood (Boscarino, Erlich, Hoffman, & Zhang, 2012;Bradley et al, 2008;Polanczyk et al, 2009;Ressler et al, 2010).…”
mentioning
confidence: 99%
“…Entretanto, todas essas técnicas terão sucesso apenas se a avaliação dos fatores ambientais for realizada de forma refinada, com rigor metodológico. Está claro que a forma como as variáveis ambientais é conceitualizada e medida influencia de forma significativa os resultados encontrados 49 . Assim, a avaliação de estressores ambientais deve estar amparada em sólidas bases conceituais.…”
Section: Perspectivas Futurasunclassified